2010
DOI: 10.1093/brain/awq053
|View full text |Cite
|
Sign up to set email alerts
|

Transmission within several spinal pathways in adults with cerebral palsy

Abstract: Many studies have investigated the changes of spinal neuronal networks in patients with cortico-subcortical or spinal lesions occurring during adulthood. In contrast, little is known about modifications of transmission within spinal networks implied in motor control for patients suffering from perinatal lesions. In the present series of experiments, we have investigated, in adult patients with cerebral palsy who suffered cerebral damage in the perinatal period, the efficacy of transmission within four spinal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 56 publications
4
62
1
1
Order By: Relevance
“…In comparison to healthy controls, postactivation depression has been found to be lower in patients with spasticity [53]. A positive correlation has been reported between the diminished postactivation depression and the severity of spasticity following stroke [54] and cerebral palsy [55]. Moreover, in subjects with spinal cord injury, postactivation depression is normal in the acute phase and becomes depressed only just before the development of spasticity [56].…”
Section: Changes In Spinal Neuronal Circuitry In Spasticitymentioning
confidence: 99%
“…In comparison to healthy controls, postactivation depression has been found to be lower in patients with spasticity [53]. A positive correlation has been reported between the diminished postactivation depression and the severity of spasticity following stroke [54] and cerebral palsy [55]. Moreover, in subjects with spinal cord injury, postactivation depression is normal in the acute phase and becomes depressed only just before the development of spasticity [56].…”
Section: Changes In Spinal Neuronal Circuitry In Spasticitymentioning
confidence: 99%
“…To avoid monosynaptic facilitation in SOL motoneurons by Ia afferences of peroneal muscle (Meunier et al 1993), we carefully checked visually and by tendon palpation that the stimulation did not induce any contraction of this muscle. The conditioning stimulus was a triple pulse over the common peroneal nerve at 300 Hz (1 ms duration), with the intensity set at 120% of TA motor threshold (Achache et al 2010). A conditioning test interval was determined for each participant by testing several intervals between 15 and 25 ms, with 1 ms steps.…”
Section: Pns (Sessions 3 and 4)mentioning
confidence: 99%
“…Previous studies have revealed a significant positive correlation between reduced post-activation depression and spasticity severity 6,7 . Our results provide additional evidence for this relationship.…”
Section: A B Discussionmentioning
confidence: 90%